SAXITOXIN IN GREEN MUSSELS (Perna viridis, Mytiliae), BLOOD COCKLE (Anadara granosa) AND FEATHERS COCKLE (Anadara antiquata, Arcidae) USING HIGH PRESSURE LIQUID CHROMATOGRAPHY - Winarti Andayani; Agustin Sumartono (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Saxitoxin (STX) was measured in green mussels (Perna viridis), and feathers cockle (Anadara antiquata, Arcidae) from Jakarta and blood cockle (Anadara granosa) from Jakarta and Indramayu. Samples were taken 7 times from fish market Muara Baru Jakarta and Karangsong Indramayu. All samples were collected from June up to October 2009. The aim of this research is to find out the content of STX in the mussels. The mussels tissues were homogenized, weighed and extracted with 0.1 M HCl. The supernatan were filtered by 0.45 μ nylon membran. Fluorescence oxidation of STX was carried out using 2% H2O2 in alkaline solution. Analysis was performed using HPLC equipped with a C18 column (4.6 mm×250 mm, 5 μm), fluorescence detection (ex 340 nm, em 400 nm) elution of acetonitrile/0.1 M ammonium formate solution (5:95, v/v, pH 6) at a flow rate of 1.0 ml/ min. The calibration graphs was prepared by injecting standards ranging from 0,5–20 ng/ml, giving an acceptable linearity (r = 0.999). Retention time of saxitoxin standard was detected at 5.467 min. Negative results were obtained for most of blood mussels from Indramayu with the exception of the 4th and 7th sampling. Saxitoxin were detected in Perna viridis and Anadara antiquata, Arcidae ranging from 0.87–5.39 µg/ 100 g and 0.14–0.9 µg/ 100 g wet tissues respectively.